PENGARUH INFLASI, KURS DAN SUKU BUNGA TERHADAP RISIKO SISTEMATIS SEBAGAI VARIABEL MEDIASI DAN IMPLIKASINYA TERHADAP HARGA SAHAM DENGAN PENERAPAN REGRESI DATA PANEL COMMON EFFECT - -, Sunaryo (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
The aims of this research are to examine the direct effect and indirect effect of Inflation, Exchange Rate, Interest Rate on Stock Price with Systematic Risk as an intervening variable. This research sample is shared in the sharia category in the JII group (Jakarta Islamic Index) listed on the Indonesia Stock Exchange (IDX) period 2013-2018 by using a purposive sampling method. There were 41 stocks selected as samples. The method of analysis used is Path Analysis, the development of panel data regression common effect. Using panel data regression with common effect analysis, it is known that the Inflation and Exchange Rate has a positive significant effect on Systematic Risk. However, Interest Rates have a significant negative effect on Systematic Risk. Systematic Risk has a significant negative effect on Stock Price. The path analysis results show that Systematic Risk mediates the effect of Inflation and Exchange Rates on the Stock price.